Structural behaviour of masonry arch with no-horizontal springing settlement (Fracture and Structural Integrity, 2017)
This paper presents a calculation procedure for assessing the structural integrity of a masonry arch with non-horizontal springing settlement. By applying the Principle of Virtual Work (PVW) to the deformed arch system, the procedure proposed herein details the reaction forces and thrust lines for each step of imposed settlement of the support. The procedure can also be used estimate the final displacement that causes complete failure of arch structural capacity. The results of the analysis procedure were compared against those obtained by experimental testing so as to validate the proposed calculation method.
Keywords: Safety of masonry arches; Collapse mechanism; Springing settlement; Experiment